2014
DOI: 10.2217/pgs.14.88
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Epidemiology of Pharmacogenetic Variations in CYP2C9 , CYP4F2 and VKORC1 Genes Associated with Warfarin Dosage in the Indian Population

Abstract: Based on genotypic distribution, the majority of the Indian subpopulation might require higher doses for stable anticoagulation, whereas careful assessment is required for Tibeto-Burmans who are expected to have intermediate dose requirement. This is the largest global genetic epidemiological study examining variants associated with warfarin that could potentially be valuable to clinicians in optimizing dosage strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…To avoid toxicity or treatment failure, population-based dose recommendations for drugs metabolized by CYP2C9, particularly warfarin is suggested (Giri et al, 2014;Wadelius, 2014). Most of these recommendations and dose algorithms are based on genotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid toxicity or treatment failure, population-based dose recommendations for drugs metabolized by CYP2C9, particularly warfarin is suggested (Giri et al, 2014;Wadelius, 2014). Most of these recommendations and dose algorithms are based on genotype.…”
Section: Introductionmentioning
confidence: 99%
“…However, the extent of correlation between CYP2C9 genotype and phenotype varies between populations mainly due to the contribution of sociodemographic, epigenetic, or environmental factors, such as diet. Numerous factors affecting CYP2C9 enzyme activity have been described, including genotype, gender, age, cigarette smoking, oral contraceptives, and food constituents (Bazan et al, 2014;Giri et al, 2014;Hidaka et al, 2008;Sandberg et al, 2004). These factors might be important to consider for dose modifications (Bazan et al, 2014;Lee et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As the instability by VKORC1-1639G>A polymorphism is distinct by ancestral groups 24 . The allelic distribution of VKORC11639G>A showed a great degree of high prevalence across Sudanese patients different ethnical groups, being similar to the Indian populations different ethnicities, with VKORC1-1639G>A allele frequencies which were found to be as low as 6.5% and up to 70% 25 . But, our results are quite different from the Chinese population whose genetic data had accounted for 90% of homozygous mutant VKORC1/AA genotype and only 10% of VKORC1/GA heterozygous genotype profile 26 .…”
Section: Vkorc1-1639g>amentioning
confidence: 56%
“…The following studies highlight novel discoveries that can be made, even in relatively small minority cohorts, by leveraging the genomics of non‐Europeans. A study of an Indian population showed the risk allele frequency of CYP4F2*3 (rs2108622) was higher in North Indians (30–44%), as compared with African Americans (12%), Europeans (34%), and Hispanics (23%), suggesting higher warfarin dose requirement for stable anticoagulation . A GWAS using an extreme phenotype strategy in African Americans found a novel association between a genetic variant (rs7856096) in FPGS , a gene known to affect folate homeostasis, and lower warfarin dose requirements among African Americans .…”
Section: Pharmacogenomics and Minority Populationsmentioning
confidence: 99%